Home Biofeedback for the Treatment of Dyssynergic Defecation: Does It Improve Quality of Life and Is It Cost-Effective?. (June 2019) - Rao, Satish S.C.; Go, Jorge T.; Valestin, Jessica; Schneider, John
Abstract : OBJECTIVES: Biofeedback therapy, whether administered at home or in office settings, is effective for dyssynergic defecation (DD). Whether home biofeedback improves quality of life (QOL) and is cost-effective when compared with office biofeedback is unknown. METHODS: QOL was assessed in 8 domains (SF-36) at baseline and after treatment (3 months), alongside economic evaluation during a randomized controlled trial (RCT) comparing home and office biofeedback in patients with DD (Rome III). Costs related to both biofeedback programs were estimated from the hospital financial records, study questionnaires, and electronic medical records. A conversion algorithm (Brazier) was used to calculate the patient's quality-adjusted life years (QALYs) from SF-36 responses. Cost-effectiveness was expressed as incremental costs per QALY between the treatment arms. RESULTS: One hundred patients (96 female patients, 50 in each treatment arm) with DD participated. Six of the 8 QOL domains improved ( P < 0.05) in office biofeedback, whereas 4 of the 8 domains improved ( P < 0.05) in home biofeedback; home biofeedback was noninferior to office biofeedback. The median cost per patient was significantly lower ( P < 0.01) for home biofeedback (1, 112.39; interquartile range (IQR), 826–1, 430) than for office biofeedback (1, 943; IQR, 1, 622–2, 369), resulting in a cost difference of 830.11 The median QALY gained during the trial was 0.03 for office biofeedback and 0.07 for home biofeedback ( P = NS). The incremental cost-effectiveness ratio was 20, 752.75 in favor of home biofeedback. Discussion: Biofeedback therapy significantly improves QOL in patients with DD regardless of home or office setting. Home biofeedback is a cost-effective treatment option for DD compared with office biofeedback, and it offers the potential of treating many more patients in the community.